Financial Auditing and Financial Reporting for Romanian State-Owned Companies– Modified Opinions and Observations - Costel Istrate (Journal of Accounting and Management Information Systems (JAMIS), 2018)
Starting with 2016, the Romanian authorities decided that 17 state-owned companies should use IFRS in their individual financial statements. The objective of this paper is to analyse how these companies have applied the accounting standards – before the transition to IFRS (2010-2017) – through the observations included in the reports delivered by the financial auditors. The main findings are: the presence of Big 4 auditors is quite limited, but in line with the situation of others categories of Romanian companies (especially the listed companies); the modified opinion are, by far, the most frequent (more than 78%). The main justifications of the modified opinions are the non-observance of the accounting rules on the provisions, followed by problems in the measurement of the assets/liabilities, and the consequences of the prudence principle. Emphasis of matters paragraph is also very present in the audit reports: the main observations in these paragraphs is about the going concern matters ant about the dependence of the state owned companies on the decisions of some public authorities.
Keywords: M42; M41; 650; state-owned companies; audit reports; modified opinions; emphasis of matter paragraph; financial reporting